2021
DOI: 10.31730/osf.io/4gdu2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the Relation Between Covid-19 Perception and Acceptance of the Covid-19 Vaccine in Kenya.

Abstract: PURPOSESince the start of the Covid-19 pandemic in 2019 in China and its spread, it continues to terrorize the Kenyan population with new infections and death cases daily. This study was done to determine if the perception of the disease influenced vaccine acceptance within the Kenyan population. METHODSElectronically shared questionnaires were used to conduct this survey in the Kenyan adult population in January and February 2021 due to Covid-19 restrictions, to evaluate the Kenyan populations’ Covid-19 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
5
2
Order By: Relevance
“…Despite the substantial decline overtime, the highest rates of vaccine acceptability were observed in Black South Africans and groups with lower socioeconomic conditions including low education and unemployment which were all significantly associated with increased odds of vaccine acceptability in all time periods. These factors have recently been associated with low vaccine acceptability in other African countries including Ghana, Kenya, and Nigeria [3,9,10,34]. In contrast to our findings, higher socioeconomic conditions have been frequently linked to vaccine acceptability and uptake in African countries such as Kenya as well as other countries [10,30,34,35].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Despite the substantial decline overtime, the highest rates of vaccine acceptability were observed in Black South Africans and groups with lower socioeconomic conditions including low education and unemployment which were all significantly associated with increased odds of vaccine acceptability in all time periods. These factors have recently been associated with low vaccine acceptability in other African countries including Ghana, Kenya, and Nigeria [3,9,10,34]. In contrast to our findings, higher socioeconomic conditions have been frequently linked to vaccine acceptability and uptake in African countries such as Kenya as well as other countries [10,30,34,35].…”
Section: Discussioncontrasting
confidence: 97%
“…We also observed a significant decline in the proportion of people who trusted the vaccine's safety and efficacy which essentially mirrored the trends observed for those who intended to receive a vaccine in all time periods. These results are not surprising since concerns around safety and efficacy of the vaccine have been strongly associated with vaccine hesitancy and widely reported globally as well as in other African populations [9][10][11][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Several studies have been conducted in East Africa to identify the level and determinants for acceptance of covid −19 vaccinations however, these studies had reported inconsistent findings, regarding the level of COVID-19 acceptance rate and determinants. Some of these studies revealed an acceptance rate of greater than 50%, 1430 while others reported less than 50%. 3137…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies have been conducted in East Africa to identify the level and determinants for acceptance of covid −19 vaccinations however, these studies had reported inconsistent findings, regarding the level of COVID-19 acceptance rate and determinants. Some of these studies revealed an acceptance rate of greater than 50%, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] while others reported less than 50%. [31][32][33][34][35][36][37] In addition, some of these studies had also shown that being male, 17,20,22,26,33,34,36 and increasing in age, 14,[19][20][21]26,38 were found to have an association with COVID-19 vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%